Спектроскопический метод регистрации ⁹⁰Sr в топливосодержащих материалах - Желтоножская, М.В. (Проблеми безпеки атомних електростанцій і Чорнобиля, 2014)
Разработана новая методика по измерению содержания ⁹⁰Sr в образцах с высокой удельной активностью ⁹⁰Sr без радиохимического выделения. Проведены измерения содержания ⁹⁰Sr в топливных фрагментах различного типа. Измерена вероятность образования Кх-излучения при радиоактивном распаде с испусканием электронов ⁹⁰Sr и ⁹⁰Y. Проведено сравнение с радиохимическими измерениями. Розроблено новий метод вимірювання активності ⁹⁰Sr в зразках з високою питомою активністю без радіохімічного виділення. Проведено вимірювання вмісту ⁹⁰Sr в паливних фрагментах різного типу. Отримано вірогідність виникнення Кх-випромінення при радіоактивному розпаді з випусканням електронів ⁹⁰Sr и ⁹⁰Y. Проведено порівняння з радіохімічними дослідженнями. The new technique is developed to measure ⁹⁰Sr in samples with a high specific activity and based on using characteristic Kx-radiation. The probability of Kx-radiation during the radioactive decay with the emission of electrons of ⁹⁰Sr and ⁹⁰Y was measured. The method for determination of ⁹⁰Sr in the fuel-containing materials was proposed from the data on the probability of ionization of atoms in β-decay. Measurements of ⁹⁰Sr were executed in fuel fragments of various types. Obtained results was compared and verified with the radiochemical research of these samples. The proposed method allows to execute the measurement of ⁹⁰Sr with an accuracy of 3-5 % in the samples with high specific activity. These results open up new possibilities in the study of radioactive materials produced as a result of nuclear fission.